Diagnostic intra-articular anaesthesia of the elbow in dogs with medial coronoid disease - Van Vynckt, D.; Verhoeven, G.; Saunders, J.; Polis, I.; Samoy, Y.; Verschooten, F.; Van Ryssen, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objective: Assessment of the effect of intraarticular anaesthesia on lameness caused by medial coronoid disease.Methods: This study included 90 dogs that were evaluated for the complaint of unilateral forelimb lameness. All dogs were suspected of having an elbow problem for which orthopaedic examination and radiographs showed inconclusive findings. Following a short sedation, mepivacaine was injected intra-articularly to determine whether lameness was caused by a suspected elbow problem. This effect was compared with the final diagnosis based on computed tomography and arthroscopy.Results: Out of 90 dogs, 78 (87%) dogs had an improvement of lameness after injection of the local anaesthetic, which confirmed the elbow joint as the primary source of lameness. A positive response was seen in all types of medial coronoid lesions. A false negative result was observed in 12 dogs (13%).Clinical relevance: Medial coronoid disease is represented by different types of pathologic lesions including chondromalacia, fissures, fragments, and medial compartment disease. Diagnosis may be difficult because of limited clinical or radiographic signs or a combination of both. Intra-articular anaesthesia can be a helpful diagnostic tool to localize the problem by eliminating pain and reducing lameness to a great extent in all types of coronoid lesions.
Keywords: Intra-articular anaesthesia; dog; mepivacaine; medial coronoid disease; arthroscopy